2016
DOI: 10.1007/s00360-016-1012-2
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic regulation of seasonal glycogen cycling in the freeze-tolerant wood frog, Rana sylvatica

Abstract: Liver glycogen is an important energy store in vertebrates, and in the freeze-tolerant wood frog, Rana sylvatica, this carbohydrate also serves as a major source of the cryoprotectant glucose. We investigated how variation in the levels of the catalytic subunit of protein kinase A (PKAc), glycogen phosphorylase (GP), and glycogen synthase (GS) relates to seasonal glycogen cycling in a temperate (Ohioan) and subarctic (Alaskan) populations of this species. In spring, Ohioan frogs had reduced potential for glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Glycogen levels reported in this study were comparable to those found in previous studies, albeit slightly lower, likely due to differences in housing and acclimation procedures (Irwin and Lee 2003 ; Storey and Storey 1985 ). Following several months of cold acclimation and aphagia, glycogen stores did not change, as observed in other freeze-tolerant frogs (Dinsmore and Swanson 2008 ; Costanzo et al 2013 ; do Amaral et al 2016 ). These data suggest that basal metabolism is being supported by other substrates, possibly proteins and lipids, contrasting with previous reports of hepatic glycogen catabolism during cold acclimation and winter months (Koskela and Pasanen 1975 ; Schlaghecke and Blüm 1978 ).…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Glycogen levels reported in this study were comparable to those found in previous studies, albeit slightly lower, likely due to differences in housing and acclimation procedures (Irwin and Lee 2003 ; Storey and Storey 1985 ). Following several months of cold acclimation and aphagia, glycogen stores did not change, as observed in other freeze-tolerant frogs (Dinsmore and Swanson 2008 ; Costanzo et al 2013 ; do Amaral et al 2016 ). These data suggest that basal metabolism is being supported by other substrates, possibly proteins and lipids, contrasting with previous reports of hepatic glycogen catabolism during cold acclimation and winter months (Koskela and Pasanen 1975 ; Schlaghecke and Blüm 1978 ).…”
Section: Discussionsupporting
confidence: 55%
“…Cold acclimation was accompanied by a shift to an 8:16 h light–dark regime. Frogs held at 5 °C were not kept in constant darkness (as in other studies, i.e., Costanzo et al 2013 and; do Amaral et al 2016), to replicate acclimation regimes from our laboratory (Zimmerman et al 2007; Goldstein et al 2010), and while photoperiod may affect some responses to cold acclimation (Stevens 1983), its effect on the development of freeze tolerance is unknown. During cold acclimation, each frog was kept in an individual container with access to water in a plastic dish, and was offered food thrice weekly until it no longer fed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations